Misty of Chincoteague - Henry, Marguerite, 1902-1997.; Dennis, Wesley (New York : Scholastic, 1947)
Two youngsters' determination to own a Chincoteague pony is greatly increased when the Phantom and her colt are among those rounded up for the yearly auction.
Originally published: Chicago : Rand McNally, 1947.
Keywords: Chincoteague pony -- Juvenile fiction; Ponies -- Juvenile fiction; Chincoteague Island (Va.) -- Juvenile fiction